Alterations in Intestinal Functionality and Bacterial Populations Following Intra-amniotic Administration (Gallus gallus) of Nicotinamide Riboside and Its Derivatives. (14th June 2022) - Kolba, Nikolai; Zarei, Amin; Cheng, Jacquelyn; Agarwal, Nikita; Dadmohammadi, Younas; Khazdooz, Leila; Abbaspourrad, Alireza; Tako, Elad
Abstract: Objectives: The primary aim of this study was to assess the effects of intra-amniotic administration of NRCl and two new derivatives (NRTBCl and NRTOCl) on BBM functionality via the evaluation of duodenal gene expression of BBM biomarkers, specifically essential digestive, absorptive and immune proteins, and the effects on cecal microbiome. Methods: We synthesized and characterized nicotinamide riboside tributyrate chloride (NRTBCl, water-soluble) and nicotinamide riboside trioleate chloride (NRTOCl) as two new ester derivatives of nicotinamide riboside chloride (NRCl). NRCl and its derivatives were assessed in vivo ( Gallus gallus ), via intra-amniotic administration (day 17 of embryonic incubation), with the following treatment groups: (1) non-injected (control); and injection of (2) deionized H2 O (control); (3) NRCl (30 mg/mL dose); (4) NRTBCl (30 mg/mL dose); and (5) NRTOCl (30 mg/mL dose). Upon injection, the effects on physiological markers involved in brush border membrane morphology, intestinal microbiota, and duodenal gene expression of key proteins were investigated. Results: NRTBCl exposure significantly increased ( p < 0.05) average cecum weight compared to other NR treatments. NR treatments significantly increased ( p < 0.05) populations of Clostridium and the NRCl treatment demonstrated significant increased ( p < 0.05) populations of Bifidobacterium, Lactobacillus, compared to the control groups (Non-injected and H2 O). Duodenal gene expression analysis revealed that NRCl, NRTBCl, and NRTOCl treatments significantly upregulated ( p < 0.05) the expression of ZnT1, MUC2, and IL6 compared to the controls, which suggests alterations in brush border membrane functionality. The administration of NRCl and its derivatives appears to trigger increased expression of digestive proteins and on the composition and function of cecal microbial populations. Conclusions: This study is the first to demonstrate alterations in duodenal gene expression and cecal microbial profiles after the intra-amniotic administration of NR and its derivatives, which have been shown to improve microbial profiles through antimicrobial effects. Thus, the present study presents strong evidence that NR and its derivatives positively modulate the intestinal microbial profile, composition, and function. Funding Sources: No external funding was utilized for the study.